Agriculture development in the Central Asia regional economic cooperation program member countries: Review of trends, challenges, and opportunities - International Food Policy Research Institute; Akramov, Kamiljon T.; Chen, Kevin Z. (Asian Development Bank, 2019)
This report takes a comprehensive look at agricultural and food systems in member countries of the Central Asia Regional Economic Cooperation (CAREC) Program. The CAREC region covers Central Asia, the South Caucasus, Mongolia, and the People’s Republic of China. Agriculture in the region has undergone extensive country-specific policy, institutional, and structural changes. These have resulted to the wide disparities in agricultural policy and levels of growth and development, which adversely affected the region’s global trade performance. The report recommends strategies to promote diversification and harmonization of cross-border customs and logistics procedures to revitalize agriculture in the CAREC region.